Gestão de resíduos sólidos na construção e montagem de empreendimentos industriais : uma contribuição da ecologia industrial - Freitas, Larissa Akemi Rosa Utiyama de (2018)
This study aims to investigate how Industrial Ecology can contribute to waste management in industrial construction. A methodology for applying Industrial Ecology practices in industrial construction sites is proposed, based on the principles of EcoIndustrial Parks. The waste management strategies adopted in two industrial construction projects in Brazil are analyzed, in order to validate the methodology proposed. The adoption of practices based on the synergies offered by geographic proximity between contractors and other actors involved is investigated, based on a set of waste management indicators and on the application of SWOT analysis technique. Results demonstrate that industrial construction projects can benefit from synergistic practices common in Industrial Ecology place-based approaches, such as the Eco-Industrial Parks. The main benefits arising from the adoption of such practices are reduction of waste disposal in landfills, administrative simplifications, uniformity in waste management practices adopted in the construction site and reduction of space occupied by waste management infrastructure in the site (better layout). Based on the results obtained, suggestions are presented to estimulate Industrial Ecology application in the construction sector.